The Gender-Environment Nexus: Towards Inclusive and Sustainable Development | As ligações gênero-ambiente: rumo ao desenvolvimento inclusivo e sustentável - Lucie Calléja (Political Observer, 2022)
Over the years, women have been associated with specific gendered roles and behaviors. In various contexts, women’s daily activities are directly linked to the environment, such as collecting clean water and producing food to sustain their families. Consequently, women across the globe are being disproportionally affected by the global environmental emergency. This paper aims at recognizing the ‘gender-environment nexus’ and raising awareness on the multiple linkages between women and environmental factors. Women’s households’ responsibilities do not only limit their opportunities outside the family sphere, such as education, economic empowerment, and political participation, but make them directly concerned with climate- and environmental-related challenges. Globally, women are actively advocating for their rights and promoting environment-compatible attitudes to enhance sustainable development. Nevertheless, women’s efforts are insufficiently acknowledged and their involvement in decision-making remains limited. Therefore, we emphasize the need to incorporate a gender lens into environmental analysis and policymaking. This paper supports the implementation of the 2030 Agenda for Sustainable Development, especially Sustainable Development Goal (SDG) 3 ‘gender equality’ and SDG 13 ‘climate action’. In this sense, we argue that women must be considered as agents of change, able to contribute to environmental sustainability, poverty eradication and planetary wellbeing.